2002
DOI: 10.1136/jcp.55.9.662
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry in the distinction between malignant mesothelioma and pulmonary adenocarcinoma: a critical evaluation of new antibodies

Abstract: Aim: The value of immunohistochemical staining in differentiating between malignant mesothelioma and pulmonary adenocarcinoma was re-examined using newly available commercial antibodies, with the aim of increasing the sensitivity and specificity of diagnosis, and simplifying the antibody panel required. Methods: Forty one malignant mesotheliomas and 35 lung adenocarcinomas were studied. Commercial antibodies to calretinin, E-cadherin, N-cadherin, surfactant apoprotein A (SP-A), thyroid transcription factor 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
101
1
11

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(122 citation statements)
references
References 32 publications
9
101
1
11
Order By: Relevance
“…The immunohistochemical detection for the nuclear expression of TTF-1 is considered as a useful marker in favor of lung or thyroid origin because of its high specificity (95-100%). [9][10][11][12] In the literature, TTF-1 expression in nuclei has been shown in rare cases of adenocarcinomas arising outside from lung or thyroid: one weakly positive case of metastatic ovarian carcinoma 13 and one focal positive case of endometrial carcinoma. 14 Recently, our group has shown one positive adenocarcinoma of colorectal origins, 8 whereas no such positivity was reported in literature ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemical detection for the nuclear expression of TTF-1 is considered as a useful marker in favor of lung or thyroid origin because of its high specificity (95-100%). [9][10][11][12] In the literature, TTF-1 expression in nuclei has been shown in rare cases of adenocarcinomas arising outside from lung or thyroid: one weakly positive case of metastatic ovarian carcinoma 13 and one focal positive case of endometrial carcinoma. 14 Recently, our group has shown one positive adenocarcinoma of colorectal origins, 8 whereas no such positivity was reported in literature ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Calretinin is expressed in both the cytoplasm and nucleus. According to the literature, its expression in malignant mesothelioma varies, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] but most authors report frequent expression in epithelioid malignant mesothelioma, with only few studies reporting expression below 90%. Interestingly, calretinin expression has been described in a wide variety of cells, including steroid-producing cells of the testis and ovary, adipocytes, eccrine-glands, keratinizing thymic epithelial cells and numerous tumors, for example Merkel cell carcinoma, Leydig cell tumors of the testis, esthesioneuroblastoma, adenomas of the adrenal gland, small cell carcinoma of the lung and adenomatoid tumor.…”
mentioning
confidence: 99%
“…The few publications that have evaluated calretinin expression in the three most frequent types of malignant mesothelioma separately present data that diverge from 18 to 100% positivity in sarcomatoid malignant mesothelioma, and 8 to 100% in biphasic malignant mesothelioma. 5,7,15,[18][19][20]33 The D2-40 staining frequency is also controversial in sarcomatoid and biphasic malignant mesothelioma. Whereas Chu et al 23 reported staining in all types of malignant mesothelioma, Ordóñ ez 24 did not detect any D2-40 staining in either sarcomatoid malignant mesothelioma or sarcomatoid areas of biphasic malignant mesothelioma.…”
mentioning
confidence: 99%
“…Most of these markers, such as BerEP4, CD15, the thyroid transcription factor (TTF-1) and carcinoembryonic antigen (CEA) stain adenocarcinomas whereas calretinin and CK5/6 are positive in both benign and malignant mesothelial cells. [3][4][5][6][7][8] An appropriate panel of antibodies is useful to differentiate between mesothelioma and adenocarcinoma. Among markers of adenocarcinomas whatever their origin (CEA, BerEP4, CD15), BerEP4 is the most sensitive (80%) but at the same time is the least specific.…”
mentioning
confidence: 99%
“…Furthermore, 22% of mesotheliomas are stained with anti-E-cadherin antibody. 3,16 MOC-31 immunostaining is also a useful marker of lung adenocarcinomas although positive immunostaining in a limited number of cells has been described in malignant mesotheliomas. 18 The mesothelioma markers group includes CK5/6 and calretinin.…”
mentioning
confidence: 99%